Kerja Etnografi dan Imajinasi Sebagai Metode Penciptaan Teater Biografi Garam - Moh Wail; Yanti Heriyawati; Rahman Saleh (Gondang: Jurnal Seni dan Budaya, 2021)
Each of art creators has their own tendencies in producing their works. The choices of form and process are significantly influenced by their cultural and aesthetical experience. The objective is to obtain the originality of the ideas and to offer novelty among the development in the field of theatre todays. This writing is aimed to reveal the creative process of the producing of a theatre work entitled Biografi Garam (The Biography of Salt). Methodologically, this is a qualitative study to describe the method or the creative process.  Ethnography and Estetika Paradoks are adopted to gain the structure of thoughts influencing the alternatives in constructing the performance aesthetic. The form of body theatre is chosen to obtain the natural structure of Madurese body as well as to release the identity to perform a free body. The creative process conducted through tubuh mengenal (the body knowing) and tubuh mengalami (the body experiencing) gives methodological experience on how the acts processed through natural body and situation becomes a theatre artwork. The background of Madurese people with all of the natural characteristics constructs the actor body so that a cultural body can be created on the stage. Ethnography and imagination process are the methods interrogating the body to become a theatre body performing Madura aesthetically to the stage. The form of a stage body is the construction result between the cultural Madura and the body execution in manifesting the ideas and imagination into an artwork that can be appreciated by the audience.